Deliberative Hermeneutics as a Critique of Khaled Abou al-Fadl’s Hermeneutics; Case Studies on Gender Issuestics of Khaled M. Abou el-Fadl - Muhammad Yaufi Nur Mutiullah (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2022)
This article seeks to criticize Khaled Abou el Fadl's negotiating hermeneutics. Abou el Fadl's hermeneutics implicitly follows the Gadamerian, which sees texts subjectively, because of which all resulting interpretations are not final but relative. Thus, Khaled Abou el Fadl's hermeneutics cannot be categorized as an emancipatory critical science. When compared and analyzed using Jurgen Habermas's discourse theory, Abou El-Fadl's hermeneutics has remained within the theoretical discourse model. The legal investigation process is performed by legal experts in monologue and not open dialogue with other interpretation communities. With this, legal decisions are made by a single subject and not Communicated with mutual understanding with the subjects other. Likewise, Abou El-Fadl states that the highest morality in determining law is discourse morality, not merely truth or precision. Using deliberative hermeneutics, the conclusion drawn from this article is that Abou el Fadl's ideas on gender issues with their negotiating hermeneutics have not been able to create an inclusive, egalitarian, and domination-free discourse in realizing a legal decision. This research is a type of qualitative research library (library research). The method used in this research is descriptive-analytical-critical. Descriptive is used to describe Khaled's understanding. Analytics is used to analyze the understanding of Khaled. Moreover, it is critical to criticize what has been described previously